The effect of antiretroviral on AIDS progression among HIV-infected people in Pahang from 2011 to 2020 - Abdullah, Nor Azlina (2021)
Background: ARV was shown to be very effective in delaying HIV disease progression. The AIDS progression rate was decrease with the usage of ARV. There was decrease in incidence of AIDS in ARV ere compared to preARV era. Sustainable Developmental Goal is aiming to end HIV/AIDS epidemic by 2030. Objectives: This study was conducted to determine median progression time from HIV to AIDS and the effect of ARV on progression to AIDS among HIV-infected people in Pahang from 2011 to 2020. Methodology: This is a retrospective cohort study using secondary data of National AIDS Registry (Pahang) and ARV Line Listing. This study included Pahang population aged 15-year-old and above who was diagnosed with HIV and registered in National AIDS Registry (Pahang) between 1st January 2011 to 31st December 2020. Exclusion criteria were patients diagnosed with AIDS within 1 month of HIV diagnosis. Patients’ vital status was updated until 21st February 2021. Kaplan Meier method was used to determine median progression time in general and between groups. Cox Proportional Hazard was used to assess the effect of ARV on AIDS progression and identify other predictive factors. Result: Kaplan Meier analysis in overall shows as the time increase, the number of event and the probability decrease. There was no median time for this Kaplan Meier analysis. The lowest survival probability was 0.790 at 112.59 months. Using cox proportional hazard, 2 final model were produced; model without CD4 count and model with CD4 count. In both models, ARV was a statistically significant factor. In model 1, ARV has 0.598 times hazard or 40.2% decrease hazard of AIDS progression. Being non-Malay reduced hazard by a factor of 0.561 or 43.9%. Increase in age and getting infected through heterosexual were bad predictors of AIDS progression. HIV infected person in age group of ≥36 years old and being infected with HIV through heterosexual had 1.343- and 1.459-times hazard towards AIDS progression. Model 2 revealed ARV uptake, higher level of education and increasing in CD4 count are good predictors for AIDS progression among HIV persons. Person who received ARV had 0.129 times hazard of developing AIDS compared with a group who did not receive ARV. Person with primary level, secondary level and tertiary level of education had 22.9%, 75.2% and 88.8% decrease in AIDS progression respectively as compared to person with no education. With every increase of 50 CD4 count, HIV person had 0.805 times hazard of developing AIDS. Conclusion: ARV was found to be effective in delaying HIV disease progression to AIDS. In the post ARV era, strategies should be focused on effective health promotion and HIV screening, early case detection, ARV initiation and adherence, in order prevent HIV transmission and halt disease progression.